Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Intravitreal Aflibercept Injection for Macular Edema Due to Central Retinal Vein Occlusion (Two-Year Results from the COPERNICUS Study) Heier JS, Clark WL Ophthalmology, 2014; 1414–20 Collagen Cross-Linking with Photoactivated Riboflavin (PACK-CXL) for the Treatment of Advanced Infectious Keratitis with Corneal Melting Said DG, Mohamed S. Elalfy MS, Gatzioufas Z, El-Zakzouk ES, Dalia G. Said DS Ophthalmology, 2014; 121: 1377-82. Changes in Postoperative Refractive Outcomes Following Combined Phacoemulsification and Pars Plana Vitrectomy for Rhegmatogenous Retinal Detachment Cho KH Am J of Ophthalmology. 2014; 158: 251-6. The utility of routine tuberculosis screening in county hospital patients with uveitis. Bryan Kun Hong, Hossein Nazari Khanamiri, Simon R Bababeygy, Narsing A Rao British Journal of Ophthalmology, 2014; 98: 1091-5.